Assessing divergent consequences of payments for ecosystem services on rural livelihoods: A case‐study in China's Loess Hills. (27th July 2018) - Li, Qirui; Amjath Babu, T. S.; Sieber, Stefan; Zander, Peter
Abstract: Payments for ecosystem services (PES) are often used as a tool for arresting land degradation and desertification. Nevertheless, deeper investigation of farm household systems (FHSs) changes during PES projects is rather limited. It is important to understand how various FHSs evolve with the divergent resource allocation strategies aiming at livelihood security in response to the PES scheme. Taking the Grain for Green Programme (GGP) in China as an example, the intended and unintended consequences of a PES scheme on land management and conservation are analyzed. Using principal component analysis and cluster analysis, FHSs types are identified, whereas composite indices regarding environmental, economic, and food security are created to assess the livelihood security of each type. This is followed by a regression analysis to explore the determinants of the livelihood security, as well as a cost–benefit analysis that investigates the multidimensional costs and benefits of FHSs types. The results show that seven distinct FHSs types evolved under the GGP PES scheme, with significant differences in livelihood security components. The strategy of setting aside the optimal share of land for ecosystem services, such as erosion reduction, and then compensating the economic loss with permanent and market‐oriented farming activities (greenhouse horticulture and orchards) can establish a positive link between economic development and environmental protection. Findings indicate that careful consideration of market, institutional, and policy interventions for supporting FHSs reorganization under PES schemes is needed to align the environmental goals with food and economic security goals of farm households, ensuring sustainability of the benefits while limiting the unintended consequences.